Novel Eye Drop Delivery Systems: Advance on Formulation Design Strategies Targeting Anterior and Posterior Segments of the Eye - Yaru Wang; Changhong Wang (MDPI AG, 2022)
Eye drops are the most common and convenient route of topical administration and the first choice of treatment for many ocular diseases. However, the ocular bioavailability of traditional eye drops (i.e., solutions, suspensions, and ointments) is very low because of ophthalmic physiology and barriers, which greatly limits their therapeutic effect. Over the past few decades, many novel eye drop delivery systems, such as prodrugs, cyclodextrins, in situ gels, and nanoparticles, have been developed to improve ophthalmic bioavailability. These novel eye drop delivery systems have good biocompatibility, adhesion, and propermeation properties and have shown superior performance and efficacy over traditional eye drops. Therefore, the purpose of this review was to systematically present the research progress on novel eye drop delivery systems and provide a reference for the development of dosage form, clinical application, and commercial transformation of eye drops.